The Socrates problem: classical solution strategies and their analytical interpretations in the studies of K. Popper and G. Vlastos. - Abdula Андрій (Actual Problems of Mind, 2022)
The Socrates problem is one of the oldest philosophical problems. Socrates is called “the founder of the Western philosophy” and “the first real philosopher”, but perhaps the Socrates we know was just a literary character in Plato’s dialogues. Even his contemporaries could not unequivocally answer the question "Who was a real Socrates?". Three ancient authors closest to him, whose works have survived (Aristophanes, Xenophon, and Plato), gave him contradictory characteristics, and later authors arbitrarily used his image. At the same time, researchers did not abandon attempts to recreate the "historical Socrates". By the end of the 19th century, there had been formed several strategies for solving the Socratic problem as a historical-philosophical and methodological problem. Based on these strategies, modern interpretations arose both in analytic philosophy and outside of it. The article examines the main approaches to solving the Socratic problem, taking into account the methodological guidelines that have been developed recently: distinguishing literary-contextual (hermeneutic) and analytic directions of research, unitary and evolutionary approaches, historically oriented analysis, etc. It also focuses the attention on two approaches representing the analytic direction of research and considered within the framework of the evolutionist paradigm for solving the problem of Socrates. These approaches are united by a general methodological guideline and a general tendency to contrast the portraits of Socrates and Plato. However, these approaches differ significantly in terms of philosophical weight and influence. The first of these approaches is presented in the works of the famous British philosopher Karl Popper, in particular, in his pivotal work The Open Society and its Enemies. In this work, Popper paid considerable attention to the figure of Socrates comparing him with Plato. For Popper, Socrates is a representative of an open, free society, while Plato is a "prophet" of a closed society. For K. Popper, solving the problem of Socrates is a philosophical justification for such an opposition; therefore, the paper draws considerable attention to this problem. The second approach represents the methodology developed by the preeminent American historian of philosophy G. Vlastos, which is characterized as "analytic developmentalism". In general, it is also aimed at finding arguments in favor of opposing the philosophy of Socrates and the philosophy of Plato. At the same time, Vlastos’s research is mainly focused on questions of historical and philosophical content. His concept is considered one of the fundamental ones in this direction of research.